PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN PENGGUNAAN ANTIBIOTIK SECARA BIJAK PADA KONSUMEN APOTEK ”X” PONOROGO - Putri, Dianita Rifqia; Setyowati, Tutut (LPPM Akafarma Sunan Giri Ponorogo, 2024)
Antibiotics are one of the main drug options for treating infections. However, if not used wisely, it will lead to resistance effects. Until now, there have been many cases of antibiotic resistance due to improper use. This research was conducted to determine the level of patients' knowledge about the use of antibiotics before and after being given education. This study uses a pre-experimental design with a one group pretest and post-test with a measuring instrument in the form of a questionnaire. The number of samples used was 78 respondents, with data collection through purposive sampling by providing education verbally and through audiovisual media. Data analysis for statistics used the Wilcoxon test. Description of the respondents' knowledge level before health education: in the good category, there were 17 (21.8%) respondents, in the sufficient category, there were 30 (38.5%) respondents, and in the poor category, there were 31 (39.7%) respondents. After health education, the results showed that in the high category, there were 58 (74.4%) respondents, in the sufficient category, there were 19 (24.4%) respondents, and in the poor category, there was 1 (1.2%) respondent. The results of the Wilcoxon test showed a value of 0.000, indicating a p-value < 0.05, thus it can be concluded that there is an influence of health education on respondents' knowledge regarding the prudent use of antibiotics.